Characterizing healthcare resource utilization in two rare diseases (Kleefstra syndrome and SLC6A1 epileptic encephalopathy) using multimodal real-world data - Caitlin A. Nichols; Ella Nysetvold; Mike Jackson; Ainslie Tisdale; Christine M. Cutillo; Shannon Rego; Ashley N. Cogell; Nelson D. Pace; Kristina Cotter (Orphanet Journal of Rare Diseases)
Abstract Background The cumulative economic burden of rare diseases surpasses that of common conditions, yet patterns of healthcare resource utilization (HRU) across rare diseases remain poorly characterized. This study leverages multimodal data collected during clinical care and through surveys to provide an in-depth evaluation of HRU across the disease journey of individuals with rare genetic diseases. Individuals with a confirmed diagnosis of Kleefstra syndrome (KS; n = 40) or SLC6A1 epileptic encephalopathy (SLC6A1; n = 30) were recruited. Structured and unstructured data were abstracted from participants’ medical records. Encounters per person-year of follow-up were calculated and compared pre- and post-diagnosis. Parents/guardians completed surveys assessing the impact of the participant’s diagnosis on their care. Results Records were available for a median of 6.4 years of follow-up from 268 unique healthcare facilities (median per patient = 4.5 facilities). Numbers of healthcare encounters were not significantly different 1 year pre- and post-diagnosis for either condition; however, the proportion of specialty encounters pre- and post-diagnosis varied significantly. Genetics encounters decreased for both conditions post-diagnosis. Cardiology, sleep medicine, and radiology encounters increased in KS post-diagnosis; conversely, audiology encounters decreased in KS post-diagnosis, and radiology encounters decreased in SLC6A1 post-diagnosis. Among specialty encounter types assessed, general practitioner (e.g. primary care, including pediatrics) encounters were the most common type for KS participants and the second-most common for SLC6A1 participants (after neurology encounters) both 1 year pre- and post-diagnosis. The number of both echocardiograms and electrocardiograms (ECG) significantly increased in KS 1 year post-diagnosis. 68% of survey respondents indicated that the participant’s care changed post-diagnosis. Conclusions Though there was no significant difference in the number of encounters pre- and post-diagnosis, significant changes in types of HRU suggest that diagnosis leads to more appropriate care and treatment. Advocacy organizations, researchers, drug developers, payors, and policymakers should consider the value of an early diagnosis to improve long-term outcomes and quality of life for patients and invest in measures that will shorten the time to diagnosis accordingly.